Effects of Low-Intensity Torque-Matched Isometric Training at Long and Short Muscle Lengths of the Hamstrings on Muscle Strength and Hypertrophy: A Randomized Controlled Study - Nakao, Sayaka; Ikezoe, Tome; Taniguchi, Masashi; Motomura, Yoshiki; Hirono, Tetsuya; Nojiri, Shusuke; Hayashi, Remi; Tanaka, Hiroki; Ichihashi, Noriaki (Journal of strength and conditioning research, 2023)
Nakao, S, Ikezoe, T, Taniguchi, M, Motomura, Y, Hirono, T, Nojiri, S, Hayashi, R, Tanaka, H, and Ichihashi, N. Effects of low-intensity torque-matched isometric training at long and short muscle lengths of the hamstrings on muscle strength and hypertrophy: A randomized controlled study. J Strength Cond Res 37(10): 1978-1984, 2023-This study investigated the effects of low-intensity torque-matched isometric training on muscle hypertrophy and strengthening at long (LL) and short muscle lengths (SL). Twenty-eight young subjects completed an 8-week hamstring isometric training program (30% of maximal voluntary contraction (MVC) × 5 s × 20 repetitions × 5 sets × 3 times/week) at 30° knee flexion (LL) or 90° knee flexion (SL). The cross-sectional area (CSA) of the hamstrings and MVC were measured before and after the intervention. The active torque because of muscle contraction was calculated by subtracting the passive torque at rest from the total torque (30% MVC). The active torque was significantly lower in the LL training group than in the SL training group (p < 0.01), whereas there was no between-group difference in total torque during training. For CSA and MVC at 30° knee flexion, the split-plot analysis of variance (ANOVA) showed no significant time × group interaction; however, it did show a significant main effect of time (p < 0.05), indicating a significant increase after training intervention. As for MVC at 90° knee flexion, there was a significant time × group interaction (p < 0.05) and a significant simple main effect of time in both the LL (p < 0.01; Cohen's d effect size [ES] = 0.36) and SL (p < 0.01; ES = 0.64) training groups. Therefore, low-intensity isometric training at LL can induce hypertrophy and strengthening, even in cases where the active torque production is lower than that at SL, whereas the training at SL may be more effective for muscle strengthening at SL.